SELF-ESTEEM AND PSYCHOLOGICAL WELL-BEING OF COLLEGE STUDENTS VICTIMS OF TOXIC RELATIONSHIPS - Putri, Septia Rachma; Huwae, Arthur (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
The phenomenon of toxic relationships among university students has increasingly attracted attention due to its serious impact on mental health, particularly on self-esteem and psychological well-being. This study aims to examine the relationship between self-esteem and psychological well-being among students who are victims of toxic relationships. The research employed a quantitative correlational method involving 71 students selected through incidental sampling. Data were collected using the Rosenberg Self-Esteem Scale (RSES) and Ryff’s Psychological Well-Being Scale (RPWBS). Data analysis was conducted using SPSS version 22 for Windows. The results revealed a significant positive correlation between self-esteem and psychological well-being (r = 0.615; p<0.01). This finding indicates that the higher the students’ self-esteem, the higher their level of psychological well-being, even when experiencing unhealthy relationships. The study emphasizes the importance of strengthening self-esteem and providing social support as crucial efforts to maintain and enhance the psychological well-being of students trapped in toxic relationships.